SPM Malay language paper II learning package / Thevi Ramasamy - Thevi, Ramasamy (2000)
SPM Malay Language learning package developed for SPM (Sijil Pelajaran Malaysia) students. It can be used as a self-study material or teaching tools in schools. SPM Malay Language learning package focuses on the proper preparation methods by providing guidelines and answering techniques to the students. It is a comprehensive tool that used to learn Malay Language effectively. The notes provided are from various researches whereas the exercises aim to help students to master the language well. The students are able to view their own performance and prepare themselves in specific topic they are weak in. This software is developed using Macromedia Director 7, which includes text, graphic, sound and animation. As a conclusion, SPM Malay Language learning package is a comprehensive learning package that helps students to achieve improvements in Malay Language.